2015
DOI: 10.1155/2015/437650
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Passive Hydrotherapy WATSU (WaterShiatsu) in the Third Trimester of Pregnancy: Results of a Controlled Pilot Study

Abstract: Background. WATSU (WaterShiatsu) is a complementary therapeutic treatment method comprising passive stretches and massage techniques administered in 35°C warm water. Pregnant women claim safe methods to reduce pain, stress, and fatigue. Therefore, we conducted a pilot study evaluating the effects of WATSU on pregnancy-related complaints in third trimester pregnant women. Methods. Nine healthy pregnant women at gestational week ≥34 were included in an intervention group (receiving WATSU) and compared to eight w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 52 publications
0
24
0
5
Order By: Relevance
“…The five RCTs in the assessment were from Korea [10], New Zealand [8], India [50], Brazil [51], and Turkey [52], and the two non-randomized controlled trials (CTs) were from Israel [53] and Switzerland [9]. Control groups underwent no treatment [9,52], massage [8], active hydrotherapy [51,53], passive stretching on land and in water [10] or were not specified [50].…”
Section: Study Designs and Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five RCTs in the assessment were from Korea [10], New Zealand [8], India [50], Brazil [51], and Turkey [52], and the two non-randomized controlled trials (CTs) were from Israel [53] and Switzerland [9]. Control groups underwent no treatment [9,52], massage [8], active hydrotherapy [51,53], passive stretching on land and in water [10] or were not specified [50].…”
Section: Study Designs and Assessmentsmentioning
confidence: 99%
“…Therefore, therapeutic indications of WATSU are reported in the literature, e.g. to address musculoskeletal conditions [8,9] neurologic diseases [10][11][12][13], and mental distress [14][15][16], to complement palliative care [17,18], or to meet the needs of cognitively impaired individuals [19][20][21][22]. Originating in the Asian philosophy of maintenance and restoration of health, WATSU can be considered as a floating massage, a tool for rehabilitation, a guided meditation to foster mindfulness and resilience, and a mediator of personal and spiritual growth [8,14,[23][24][25].However, the literature concerning WATSU appears to have been neither systematically reviewed nor evaluated to date.…”
mentioning
confidence: 99%
“…Watsu is considered to be one of the promising method for acceleration in recovery, conservative and restorative functions and the activation of afferent C-tactile fibers (Schitter et al 2015). Mooventhan and Nivethitha (2014) suggested that balanced psychomotor state with increased sympathovagal balance and level of serotonin is due to the warmth and the massage effect of water.…”
Section: Improved Cardio Vagal Baroreflex Sensitivity During Water Immentioning
confidence: 99%
“…The findings of a number of studies (Schitter et al 2015, Stan 2013, Kamioka et al 2010, Becker 2009, Geytenbeek 2002 indicated that numerous psychological and physical benefits of aquatic physical therapy. Many pyschological and functional improvements can be achieved via aquatic therapies (Inoue 2013, Kesiktas et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the buoyancy and turbulences of the water are acting on the patient's body. Reportedly, WATSU was introduced in programs that search to address stress [5,6], anxiety [7], symptoms of depression [6,7,8], posttraumatic stress disorder [7,9], and pain [5,7,10,11], and to foster awareness [5,8,12]. The purpose of this case report is to depict the gains and challenges in the use of this complementary therapy during outpatient rehabilitation.…”
Section: Introductionmentioning
confidence: 99%